Promising Immunotherapy in Metastatic Testicular Sex Cord Stromal Tumours After First-Line Chemotherapy - Shang, Bingqing; Cao, Chuanzhen; Jiang, Weixing; Shi, Hongzhe; Bi, Xingang; Cui, Chengxu; Shou, Jianzhong; Zheng, Shan; Zhang, Jin; Zhou, Aiping; Li, Changling; Ma, Jianhui (Frontiers in Immunology, 2022)
Background: Testicular sex cord stromal tumors (TSCSTs) were rare with few studies focusing on the prognosis of metastatic TSCSTs. The value of treatment including radical orchiectomy (RO) and retroperitoneal lymph node dissection (RPLND) in preventing metastasis was controversial. In addition, metastatic TSCSTs were resistant to chemotherapy. We aimed to assess the effectiveness and safety of immunotherapy in metastatic TSCSTs after first-line chemotherapy. Methods: We retrospectively screened patients with testicular tumors undergoing testis surgery between January 2005 and January 2019. Patients with TSCSTs who had received testis-sparing surgery (TSS) or RO were identified. The malignant type was defined as the metastasis occurred confirmed by the pathology. Treatment responses, progression-free survival (PFS), overall survival (OS) and safety were analyzed. Results: Among the 494 testicular tumor patients who received TSS or RO, 11(2.2%) patients with histologically proven TSCSTs were identified. Till last follow-up, 7 patients survived without tumor; 4 patients developed metastasis and received first-line cisplatin-based chemotherapy and 1 of them achieved objective response. The PFS of them were 1.5, 2.2, 9.0, and 17.0 months respectively. Two patients received immune checkpoint inhibitors (ICIs) after chemotherapy-resistance and achieved partial response till last follow-up. The median OS of 4 patients with metastatic TSCSTs was 32 months. No severe IV/V adverse events occurred. Conclusions: TSCSTs were rare and most were benign with good prognosis. ICIs represents a promising option for improving clinical benefits in metastatic TSCSTs.